Prediction of Landing and Take-off of Aircraft based on the Weather Using Fuzzy Logic - ., Robbi Rahim (International Journal of Advanced Science and Technology, 2019)
The aircraft is an air transport tool that can deliver passengers to specific destinations very quickly. The aircraft does not have bottlenecks when it is airborne. The plane runs by using a predetermined route without having to turn. However, in traveling, planes must anticipate several things. Several parameters determine a plane to fly and land. This activity is an activity where the aircraft must be very careful. Visibility, wind direction, and wind speed are three things to watch out for. Fuzzy logic can predict whether an aircraft is suitable for flight or landing. MatLab can be used to determine the analysis value of the three variables in order to determine whether the aircraft can fly or land on these conditions. By calculating the results of the analysis by the fuzzy method, the aircraft can land or fly correctly.